Réponses

Meilleure réponse !
2014-05-03T12:08:52+02:00
(3x - 4)(8 + 2x) = 0
Une équation produit est nulle si l'un de ses facteurs est nul. donc :
3x - 4 = 0                                  8 + 2x = 0
3x = 4                                            2x = -8
x = 4/3                                             x = -4

36x² + 12x + 1 = 0
(6x)² + 6*2x + 1² = 0
(6x + 1)² = 0
donc :
6x + 1 = 0
6x = -1
x = -1/6

9x² - 81 = 0
(3x)² - 9² = 0
(3x - 9)(3x + 9) = 0
donc :
3x - 9 = 0                                ou 3x + 9 = 0
3x = 9                                               3x = -9
x = 2                                                   x = -3